Interactions between the human milk oligosaccharide 2′-fucosyllactose and Bifidobacterium longum subspecies infantis in influencing systemic immune development and function in piglets - Daniels, Victoria C.; Monaco, Marcia H.; Hirvonen, Johanna; Ouwehand, Arthur C.; Jensen, Henrik Max; Mukerjea, Ratna; Christensen, Niels; Lehtinen, Markus J.; Dilger, Ryan N.; Donovan, Sharon M. (Frontiers in Nutrition, 2024)
Introduction The oligosaccharide 2′-fucosyllactose (2′-FL) is a predominant component of human milk, serving as a prebiotic for gut microbiota and influencing immune development in infants. Bifidobacterium longum subspecies infantis (B. infantis) is a commensal bacterium found in breastfed infants. Both 2′-FL and a specific strain of B. infantis, Bi-26™, are commercially available. This study investigates the potential synbiotic relationship between 2′-FL and Bi-26™ on immune development. Methods Two-day-old piglets (n = 53) were randomized in a 2 × 2 design, receiving either a commercial milk replacer ad libitum without (CON) or with 1.0 g/L 2′-FL (FL). Piglets in each diet were further randomized to receive either glycerol stock alone or Bi-26™ (109 CFU) (BI and FLBI) orally once daily. On postnatal day (PND) 34/35, animals were euthanized, and blood was collected for serum cytokine analysis. Additionally, peripheral blood mononuclear cells (PBMCs) were isolated for ex vivo stimulation and flow cytometry analysis. Serum and ex vivo cytokines were analyzed using a multivariate model. All other outcomes were analyzed using a two-way ANOVA, considering prebiotic and probiotic fixed effects. The significance level was set at a p value <0.05, with trends reported for 0.05 < p < 0.1. Results Immune cell populations in PBMCs were unaffected by the experimental treatment. However, serum interleukin (IL)-1RA, IL-1β, IL-12, and IL-18 were all higher (p < 0.05) in the FL group than in the CON group. In isolated PBMCs, lipopolysaccharide (LPS) stimulation resulted in higher IL-1RA and a trend for higher IFN-γ secretion in the FL group vs. the CON group. Conclusion 2′-FL stimulates a balanced cytokine profile in healthy piglets without changing immune cell populations. When immune cells are stimulated ex vivo with LPS, 2′-FL primes T-cells for a proinflammatory response, which is moderated by co-administration of Bi-26™.